Implementation of Online and Offline Building Information System based on Virtual Reality and Augmented Reality - Ganiev, Asilbek; Sun Shin, Ho; Hee Lee, Kang (International Journal of Engineering and Technology, 2018)
Modern people can use navigation on the outside to save time and get to the destination well. Likewise, in order to find out more information about a destination building, such a system is increasingly needed both in front of the computer (on-line) of the house and after reaching the destination in the building (off-line). Accordingly, we employ Building Information System (BIS) as a system that provide users with content related to a building like BIO and BIM. The Building Information Online system (BIO) is an interactive map application designed to assist customers in finding parcels and building on a map online. The Building Information Modeling (BIM) allows nD information to be visualized simultaneously by architects, engineers and constructors to gain a synchronized understanding viewing from different perspectives. Inspired by above researches, we implement a service that provides online and offline Virtual Reality (VR) and Augmented Reality (AR) content for a building. This system can provide users outside the building with information within the building via devices with VR and AR support regardless of space restrictions. The system is designed to operate across scenarios requiring offline, online, offline-online collaboration, etc., and the corresponding experiments are carried out.Â Â